2009
DOI: 10.1295/polymj.pj2008334
|View full text |Cite
|
Sign up to set email alerts
|

Silane-Bridged Electroless Ni-Plating on Submicron Polymer Spheres

Abstract: The silane coupling agent (3-trimethoxysilyl propryl methacrylate) was used to functionalize the surface of submicron polymer spheres (sized 168-650 nm) for bridging the polymer core (polystyrene crosslinked with divinylbenzene) and the metal coating shell. The submicron polymer spheres were synthesized by emulsifier-free emulsion polymerization in the presence of NaOH. The metal shell was created by electroless plating. The performance of silane coupling agent, as the bondage between the core and the shell, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recent works , have demonstrated that the grafting of complexing groups on various substrates (gold, silica, polyimide) may allow satisfactory metallization, but these processes are inappropriate for ABS, the most widely electroless plated plastics. In our case, the interphase will be a thin polymer film (poly(acrylic acid), PAA) truly grafted on the ABS surface using a new grafting technology named GraftFast developed in the Laboratory of Chemistry of Surfaces and Interfaces , .…”
Section: Introductionmentioning
confidence: 99%
“…Recent works , have demonstrated that the grafting of complexing groups on various substrates (gold, silica, polyimide) may allow satisfactory metallization, but these processes are inappropriate for ABS, the most widely electroless plated plastics. In our case, the interphase will be a thin polymer film (poly(acrylic acid), PAA) truly grafted on the ABS surface using a new grafting technology named GraftFast developed in the Laboratory of Chemistry of Surfaces and Interfaces , .…”
Section: Introductionmentioning
confidence: 99%
“…However, because of the future European ban on chromium waste, that efficient process has to be replaced , . Recent works, based on a technological breakthrough, consist of the formation of a robust interphase between the substrate surface and the metallic layer which is intended to replace the rough interface which usually results from the chromic acid treatment , . For example, block copolymers with one block designed to interpenetrate the polymer substrate and the other one bearing chelating groups (such as poly(acrylic acid) (PAA)) were recently used to form a host polymer film for electroless plating on various polymer substrates .…”
Section: Introductionmentioning
confidence: 99%
“…It could be attributed to the incorporation of bulky pendant groups and presence of flexible linkage in the polymer due to which there would be a considerable decrease in the rigidity and a lowering of energy of internal rotation for the polymer chain, thus reducing the crystallinity and improving the solubility. 18 Polyaspartimides containing pyridine moiety exhibit better solubility in comparison with p-phenylene moiety, though the presence of pyridine group should enhance the polymer rigidity. The incorporation of bulky pendant group in the polymer chain decreases the intermolecular forces between the polymer chains, because of looser packing of polymer chains.…”
Section: Solubilitymentioning
confidence: 99%